2002
DOI: 10.1152/ajprenal.00228.2002
|View full text |Cite
|
Sign up to set email alerts
|

Manganese superoxide dismutase gene therapy protects against irradiation-induced cystitis

Abstract: Urinary bladder cystitis occurs in patients receiving radiation therapy for pelvic tumors. Radiation-induced formation of superoxide radicals is believed to damage the urothelium, exposing the underlying bladder smooth muscle to urine, culminating in nerve irritation and muscle dysfunction. We tested whether overexpression of MnSOD could decrease superoxide levels and protect the bladder from radiation damage. Pelvic irradiation led to sloughing of urothelial umbrella cells, with decreased transepithelial resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 42 publications
(45 reference statements)
2
54
0
Order By: Relevance
“…Irradiated urinary bladders in animal models undergo pathological changes in three phases. 25 The first phase is the acute damage consisting of urothelial swelling, ulceration, and vascular endothelial cell damage. 26,27 The second phase is the infiltration of inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…Irradiated urinary bladders in animal models undergo pathological changes in three phases. 25 The first phase is the acute damage consisting of urothelial swelling, ulceration, and vascular endothelial cell damage. 26,27 The second phase is the infiltration of inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…51 However, by using a construct of the Cu/ZnSOD transgene to which was attached the mitochondrial localization signal of MnSOD, an effective transgene protein for radioprotection was demonstrated. 51 MnSOD-PL administration prior to irradiation of lung, 12 oral cavity, 21 esophagus, 17 bladder, 22 and intestine 23 has Lung irradiation protection by inhalation of MnSOD-PL M Carpenter et al been shown to provide radioprotection in each organ's target volume. In two model systems (lung and oral cavity), orthotopic tumors were not detectably protected from irradiation killing under conditions of normal tissue radiation protection.…”
Section: Lung Irradiation Protection By Inhalation Of Mnsod-pl M Carpmentioning
confidence: 99%
“…2,3,5,6 A biological response modifier approach toward decreasing pulmonary toxicity would be valuable to facilitate new improvements in radiation treatment. We have demonstrated that organ-specific (lung, [12][13][14][15][16] esophagus, [17][18][19][20] oral cavity, 21 bladder, 22 or intestine 23 ) introduction of the human manganese superoxide dismutase (MnSOD) transgene by plasmid/liposomes (MnSOD-PL) or viral vectors is associated with significant uptake, increased transgene mRNA and protein availability for 48-72 h after administration, and significant protection from ionizing radiation-induced acute and chronic organ injury. 24 In both pulmonary and esophageal radiation protection models, intratracheal or intraoral administration of MnSOD-PL was shown to delay the onset of organizing alveolitis/fibrosis and esophagitis in C57BL/ 6J mice, respectively, and improve overall survival in single-or multifraction radiotherapy protocols.…”
Section: Introductionmentioning
confidence: 99%
“…If future studies confirm that SOD2 expression are associated with a tumor residual or confer a radioresistance when a particular radiation treatment-planning method is used, then identifying patients with tumors that carry increased SOD2 may improve treatment selection. Furthermore, regulating the expression of SOD2 in vitro and in mouse model has improved the sensitization of cell lines and experimental tumors to radiation therapy, or the protection of the haematopoietic compartment and normal tissues from the effects of ionizing radiation, demonstrating the effectiveness of a combination of gene therapy and conventional radiotherapy (10,15,(44)(45)(46). Accurate detection of SOD2 status prior to therapy will also allow SOD2 inhibitors or radiosensitizers to be used in clinical trials in NPC to reduce failure from radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying SOD2 gene could therefore yield crucial insights into the genes in radioresistant phenotypes. ONCOLOGY REPORTS 23: 1005-1011, 2010 The effect on radioresistance of manganese superoxide dismutase in nasopharyngeal carcinoma…”
Section: Introductionmentioning
confidence: 99%